Динаміка значень параметрів кривих lm грошових ринків для 25 регіонів України у 2003-2009 р.р. - Горбачук, В.М. (Культура народов Причерноморья, 2013)
Депозити домогосподарств були краще диверсифіковані у 2009 р. по Україні, ніж депозити нефінансових корпорацій і некомерційних організацій. На макроекономічному рівні України, без регіональної деталізації, зниження кредитної маси нефінансових корпорацій спостерігалося тільки у лютому 2009 р. під час банківської паніки, коли кредитна ставка для Києва та Київщини атипово перевищувала таку ставку для України. Під час кризи знак чутливості грошової маси до відсоткової ставки перестав відповідати теоретичному для Запоріжчини, Івано-Франківщини, Києва та Київщини, Полтавщини. Ключові слова: грошова маса, відсоткова ставка, кредити, депозити. Депозиты домохозяйств были лучше диверсифицированы в 2009 г. по Украине, чем депозиты нефинансовых корпораций и некоммерческих организаций. На макроэкономическом уровне Украины, без региональной детализации, снижение кредитной массы нефинансовых корпораций наблюдалось только в феврале 2009 г. во время банковской паники, когда кредитная ставка для Киева и Киевщины атипично превышала такую ставку для Украины. Во время кризиса знак чувствительности денежной массы к процентной ставке перестал соответствовать теоретическому для Запорожчины, Ивано-Франковщины, Киева и Киевщины, Полтавщины. Ключевые слова: денежная масса, процентная ставка, кредиты, депозиты. The deposits of households had better diversification over Ukraine in 2009 that those of nonfinancial corporations and noncommercial organizations. At the macroeconomic level of Ukraine, without regional details, the reduction for credit aggregate of nonfinancial corporations has been observed in February 2009 only during the banking panic, when the loan rate for Kyiv and Kyiv region atypically exceeded that for Ukraine. The dynamics for credit aggregate of households for Ukraine as a whole was typical for each individual region – reduction every month but August 2009, wherefrom the option of using a representative household follows. Modeling for loans of nonfinancial corporations requires taking into account regional particularity. The dynamics of total credit aggregate for Ukraine as a whole was typical for each individual region except a few regions: reduction in February–May and October–December 2009. Contrary to the deposits of nonfinancial corporations, the deposits of households for Ukraine as a whole have increased during 2009 but February, March, September. Measuring parameters of regional money markets with accounting for the 2008–2009 data and comparing with their pre-crisis values based on the 2003–2007 data showed during the crisis the sign for sensitivity of money aggregate to interest rate ceased to correspond to the theoretically explained for Kyiv and Kyiv, Zaporizhzhya, Ivano-Frankivsk, Poltava regions. Key words: money aggregate, interest rate, loans, deposits.